2019
DOI: 10.1080/15309576.2019.1700806
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Performance Measurement Systems in Local Governments: Moving from the “How” to the “Why”

Abstract: This paper examines how Performance Measurement Systems (PMSs) are implemented in local governments where the initial context is defined by equivalent external pressures and professional expertise, in order to address the question of "why" PMS implementation patterns differ from one setting to another. The study explored the reasons behind these different patterns in a context where local governments responsible for providing a local service implemented a PMS with the direct support of professional experts, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Thus, as these authors argued, it is recommendable to have a situation approach to performance management. Similarly, Agasisti et al (Agasisti, Agostino, & Soncin, 2019) show that certain factors determines heterogeneity among PMM systems. Fitness of use appears with uncertainty, complexity and the bureaucratic culture.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, as these authors argued, it is recommendable to have a situation approach to performance management. Similarly, Agasisti et al (Agasisti, Agostino, & Soncin, 2019) show that certain factors determines heterogeneity among PMM systems. Fitness of use appears with uncertainty, complexity and the bureaucratic culture.…”
Section: Discussionmentioning
confidence: 89%
“…Our starting point was that PMM systems have different types of uses (diagnostic and interactive) and that, depending on the context, one use may be more productive. Previous research has shown a low level of use of PMM systems, despite the great number of implementers (George et al, 2018;Gerrish, 2016) and has focused on identifying the key characteristics of the organizations that use performance measurement (Agasisti et al, 2019;Ammons & Rivenbark, 2008;Torres et al, 2011;Yetano, 2009). It seems clear that the use of performance management systems by itself does not produce results (Gerrish, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Performance measurement is one result of the New Public Management (NPM) concept, which focuses on the accountability of managing public organizations (Osborne, 2006). To date, the institutional issues of NPM remain contentious (Hood & Dixon, 2015;Tallaki & Bracci, 2019) because the ongoing public sector reforms attract a lot of attention (Agasisti, Agostino, & Soncin, 2020;Modell, 2021Modell, , 2022Raboca, 2021;Tran & Nguyen, 2020) and the implementation of PMS is one alternative choice in public sector reform. The use of PMS as part of the public sector reform agenda (Cavalluzzo & Ittner, 2004;de Lancer Julnes & Holzer, 2002;Kurniawan & Akbar, 2021;Modell, 2001;Parwoto & Halim, 2020;Speklé & Verbeeten, 2014;Tran & Nguyen, 2020;Wijaya & Akbar, 2013).…”
Section: Introductionmentioning
confidence: 99%